How can we design low back pain intervention studies to better explain the effects of treatment? - Mansell, G.; Hill, J.; Kamper, S.; Kent, Peter; Main, C.; van Der Windt, D. (Lippincott, Williams and Wilkins, 2014)
The majority of trials investigating the effectiveness of primary care interventions for back pain have shown small or at best, moderate effects of treatment 36 , 37 and the fi eld is looking for better ways to improve outcomes for patients with back pain. Mediation analysis aims to provide better insight into the causal pathways underlying treatment effects, explaining why treatments work or do not work and potentially offering new opportunities to improve patient outcomes by optimizing the content or delivery of treatment. Until recently, mediation analysis in clinical research was often limited to a descriptive evaluation of the processes potentially underlying the effects of treatment in trials. 38 , 39 During the past few years, interest in the use of more sophisticated approaches to mediation analysis has increased, often guided by methods described in the psychological literature. In this article, we have summarized the concepts and different designs used in mediation analysis and explained the importance of experimental designs when investigating mediators of treatment effect. We have also emphasized the importance of other considerations such as defi ning and understanding constructs, selecting study measures with appropriate measurement properties, and ensuring study measurement time points are appropriately selected, to investigate the longitudinal associations between mediating and outcome variables. We have also outlined the relevance of observational and qualitative research in identifying potential mediating factors. On the basis of the discussions during the 2012 workshop and supported by the literature, we have proposed a set of recommendations to support and improve the design of mediation analysis in back pain research (Box 1), with the ultimate aim to improve the design and delivery of intervention studies and optimize outcomes for patients with back pain. © 2014 Lippincott Williams and Wilkins.